Nearpod-based physical education learning and its implications for students' self-confidence: A systematic literature review - Novriansyah Novriansyah; Muhammad Maulana Fajar; Fitri Agung Nanda; Muhammad Idrus; Rizkei Kurniawan (Bima Loka: Journal of Physical Education, 2026)
Abstract Self-efficacy is a key factor influencing students' participation, motivation, and performance in Physical Education (PE) learning. This study aims to examine the potential of the interactive learning platform Nearpod in enhancing students' self-efficacy in PJOK through a Systematic Literature Review (SLR). A qualitative descriptive approach was employed by analyzing secondary data from peer-reviewed journal articles and research reports indexed in Google Scholar, ERIC, Scopus, ScienceDirect, and SINTA. The review indicates that Nearpod's interactive features, including quizzes, interactive videos, virtual reality experiences, and collaborative activities, promote active student engagement, provide immediate feedback, and foster a supportive and non-threatening learning environment. These learning conditions correspond to Bandura's four sources of self-efficacy—mastery experiences, vicarious experiences, social persuasion, and physiological and affective states—thereby strengthening students' confidence in performing movement tasks and participating in physical activities. The findings suggest that Nearpod has considerable potential as an innovative instructional tool for developing students' self-efficacy through interactive, student-centered learning in PE. It is recommended that PJOK teachers integrate Nearpod into instructional practices, while future empirical studies should investigate its effectiveness across diverse educational contexts.